Եզրույթների թարգմանությունը հայ միջնադարյան աստվածաբանության մեջ - Խ. Վ. Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
Сравнение оригинального греческого текста 3-го и 4-го анафематизмов св. Кирилла Александрийского с разными армянскими переводами выявляет существенную неоднозначность армянских переводов терминов «ипостасис» (ипостась) и «просопон» (лицо), что нашло отражение в работах современных богословов. Comparison of the Greek original text of 3rd and 4th anathemas of St. Cyril of Alexandria and the Armenian translation of that text in different sources shows serious discrepancies in the Armenian equivalents of the theological terms such as “hypostasis” and “prosopon” (person). These discrepancies often are transferred to the works of modern theologians.
Keywords: B Philosophy; Psychology; Religion; Language and Literature; Practical Theology; Translation and interpretation